2021
DOI: 10.1016/j.biochi.2020.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Potential physio-pathological effects of branched fatty acid esters of hydroxy fatty acids

Abstract: Branched Fatty Acid Esters of Hydroxy Fatty Acids (FAHFAs) are a new endogenous lipid class with recently uncovered interesting biological effects and which have been detected in food of plant and animal origins. Some FAHFAs can improve glucose tolerance and insulin sensitivity, stimulate insulin secretion, and exert anti-inflammatory effects. Other beneficial health effects have also been suggested, in particular against some cancers. FAHFAs could therefore be a potential therapeutic target for the treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…FAHFAs are recently discovered as endogenous lipid metabolites with multiple bioactivities such as anti-inflammatory [ 2 ], anti-diabetic [ 2 , 11 ], anti-apoptotic activities [ 3 ], and also promote browning of white adipose tissue [ 17 ]. Despite their structural diversity with more than 300 regioisomers [ 5 ], to date, the PAHSA family is the most studied [ 1 , 5 , 8 ]. The studies focusing on the effects of polyunsaturated FAHFAs such as ω-3 (DHALA and EPAHSA) and ω-6 (LAHLA) fatty acids are limited.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…FAHFAs are recently discovered as endogenous lipid metabolites with multiple bioactivities such as anti-inflammatory [ 2 ], anti-diabetic [ 2 , 11 ], anti-apoptotic activities [ 3 ], and also promote browning of white adipose tissue [ 17 ]. Despite their structural diversity with more than 300 regioisomers [ 5 ], to date, the PAHSA family is the most studied [ 1 , 5 , 8 ]. The studies focusing on the effects of polyunsaturated FAHFAs such as ω-3 (DHALA and EPAHSA) and ω-6 (LAHLA) fatty acids are limited.…”
Section: Discussionmentioning
confidence: 99%
“…We assume that activation of NRF2 by 12-DHAHOA could be the cause for increased TAGs in C3A cells. Moreover, previous studies have also demonstrated the abundance of FAFHFA-TAGs over white adipose tissue and are believed to be an important reservoir of FAHFAs in cells and tissues [ 5 ]. They also reported that FAHFAs are incorporated into TAGs by the action of diacylglycerol acyltransferases DGAT1 and DGAT2 in adipocytes in vitro [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to note that these health effects of FAHFAs have been demonstrated with pharmacological doses in animal models or linked to circulating FAHFAs levels, but not associated to diet normal content. Several comprehensive reviews on branched FAHFAs have been recently published (Brejchova et al, 2020;Benlebna et al, 2021).…”
Section: Health Effectsmentioning
confidence: 99%